Pengaruh Motivasi dan Budaya Organisasi Sekolah terhadap Kinerja Guru melalui Disiplin Kerja - Sadikun; Indra Prasetyo; C. Sri Hartati (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study was to describe motivation, school organizational culture, work discipline and teacher performance in the Office of the Regional Coordinator for Education, Rangsang District, Meranti Islands Regency and to analyze the influence of motivation and school organizational culture on teacher performance with teacher work discipline as an intervening variable. This research using a quantitative approach. The population in this study were 54 teachers in the Regional Coordinating Office for Education, Rangsang District, Meranti Islands Regency, the sample in this study was determined as many as 54 people using the census sampling method. This study uses the SEM method with PLS. The results showed that Motivation, Organizational Culture, Work Discipline and Teacher Performance Coordinator of the Education and Culture Subdistrict District of Rangsang Meranti Islands Regency were good, the effect of motivation on discipline was positive and significant, organizational culture on discipline was positive and insignificant, motivation on performance is positive and significant, organizational culture on performance is positive and not significant, discipline on performance is positive and significant, motivation on performance in intervening work discipline is positive and significant, organizational culture on performance is intervened by discipline work is positive and not significant